Designing Strategic Agility in Inclusive Digital Business Models: A Conceptual Framework for Resilient Agri-Entrepreneurship in Himalayan Economies - Paudel, Dolendra (International Journal of Atharva, 2026)
Agricultural entrepreneurship in Himalayan economies faces compounding challenges such as geographic isolation, fragmented markets, institutional voids, climate variability and limited infrastructure. Inclusive Business Models (IBMs) have emerged as a promising response, however most inclusive agri enterprises struggle to scale because they lack the strategic flexibility needed to respond to a rapidly shifting environment. This study addresses that gap by developing the Strategic Agility in inclusive Digital Business Models (SA-IDBM) framework, a conceptual model that integrates strategic agility theory dynamic capabilities, and inclusive innovation literature to explain how agri-enterprises in resource constrained mountain economies can build multidimensional resilience. Based in an integrative conceptual synthesis of interdisciplinary literature, the framework identifies four mutually reinforcing enablers which are digital sensing capabilities, adaptive strategic decision-making, inclusive value co-creation, and learning-reconfiguration mechanisms. These enablers operate recursively by forming an agility loop and are more moderated by the distinctive Himalayan context. Four theoretically grounded propositions are advanced to guide future empirical research. A key conceptual contribution is the reconceptualization of digital technologies not as efficiency tools but as strategic-social enablers that simultaneously strengthen organizational adaptability and social inclusivity. The framework extends strategic agility theory into subsistence-oriented and inclusive market contexts largely overlooked in mainstream strategy literature, and offers actionable guidance for entrepreneurs, policymakers, cooperatives and development organizations working in the vulnerable Himalayan region.